IDENTIFIKASI sEMG PADA WANITA PEMAKAI SEPATU BERHAK TINGGI MENGGUNAKAN METODE FFT - I Dewa Gede H.W; Priyambada Cahya N; Liliek Soetjiatie; Triana Rahmawati (JURNAL PENELITIAN KESEHATAN, 2015)
"Wearing High Heel, Face Smiling, Heart Screaming", that's the headlines of one women'smagazine in Indonesia. Shoes are one of which had a role in the activity of a woman.Shoes have health function and aesthetics. Several studies have reported that theproportion of the prevalence of foot problems in women is associatedwith the use of high heels.One of the health problems caused by high heels is osteoarthritis. Symptoms include pain andstiffness in muscles and joints of bones. In the lower stage, a complaint can be treated withmedication and exercise movement. In later stages require surgery replacement cushions joints. Basedon the effects of the joints and muscles of the foot, the research about the use of high-heeled shoesnecessary.This study uses the FFT method that generates the frequency spectrum of the EI\1G signal on thegastrocnemius muscle and soleus muscle. The results of the frequency spectrum of thesignal provided an information about the content of the signal frequency form. Afterobtained the spectrum of the signal is, then it's calculated Mean Power Frequency(MPF).In this study, MPFvalue on the soleus muscle produced the 100-200 Hz frequency, the gastrocnemiusmuscleshowed a lower frequency than the soleus muscle 60-80 Hz frequency. The use of high heels7 Cm affect the soleus muscle increasing in the frequency ofthe initial frequency of 100-120 cm be180-200 Hz frequency. The use of high shoes with different rights can be classified clearly in the soleusmuscle MPF.It shows that the soleus muscle a major effect on height heel imposed on respondents. Theuse of high heels from 3 cm to 7 cm does not change the frequency of gastrocnemius muscle.Frequencyare still remain 60-80 Hz.KEYWORDS: Signals, Frequency, Muscles, Shoes